THE RELATIONSHIP BETWEEN ORGANIZATIONAL SUPPORT, JOB SATISFACTION, ORGANIZATIONAL COMMITMENT TO ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON EMPLOYEES OF TAMAN TEBING BREKSI TOURISM DESTINATION - Adistyana, Mutiara Dwiarti; Khoirunnisa, Rikha Muftia (Jurnal Perilaku dan Strategi Bisnis, 2023)
This research aims to determine simultaneous and the partial effect of perceived organizational support, job satisfaction, and organizational commitment to organizational citizenship behavior on employees of Taman Tebing Breksi (TTB) Destination Tourism, This is a quantitative research. This research uses primary data, collected by questioner, This research population are 112 employees and the research sample are 88 employees. The validity in this research use Confirmatory Factor Analysis (CFA). The reliability test in this research use Cronbach Alpha. The utilized analysis method is multiple regression analysis, Â This research results that perceived organizational support, job satisfaction, and organizational commitment simultaneously influence organizational citizenship behavior on employees of TTB Tourism Destination, perceived organizational support has positive partially influence organizational citizenship behavior on employees of TTB Tourism Destination, job satisfaction has positive partially influence organizational citizenship behavior on employees of TTB Tourism Destination, and organizational commitment has positive partially influence organizational citizenship behavior on employees of TTB Tourism DestinationThe obtained research suggestions are the management must hold on to and must boost perceived organizational support, job satisfaction, and organizational commitment that has been proven to have a positive impact to OCB on employees of TTB Destination.